TEACHER'S STRATEGY IN BUILDING LANGUAGE AWARENESS THROUGH JOYFUL LEARNING - Ubay Ubay; Mualim Wijaya; Nafhatul Widad (JURNAL AL-TANZIM, 2021)
This research is based on integrating multi-disciplinary science to create effective and efficient learning, namely education management, psychology, Arabic language education which are mixed into a single unit. This study aims to understand the teacher's strategy in building Arabic awareness through joyful learning, especially in developing maharatul kalam for students at SMP Nurul Jadid. This study uses a descriptive qualitative approach with a case study type, where the researcher uses interviews, observations, and documentation to collect data. Furthermore, the data obtained are reduced, presented, and concluded according to the themes studied. The results showed that the teacher's strategy in building Arabic awareness through joyful learning in developing students' maharatul kalam at school was carried out through; smart language games, puzzles, quizzes, listening to songs, presentation of information. This research has implications for the importance of developing strategies and teaching materials in building children's motivation to achieve the desired goals.